Ecological perspectives of the endangered ethnic minority languages and culture in China - Ng, Boon Sim; Mamat, Roslina; Yu, Jianbin; Mustapha, Nik Farhan (Penerbit Universiti Malaysia Pahang Al-Sultan Abdullah, 2024)
The chapter focuses on the ecology of the ethnic minorities language and culture in China. Various related studies were discussed with intention of highlighting the endangered situation experiencing by these communities. Therefore, the last section highlights on language planning efforts in preserving the threatened language and culture.